The Role of Kamco in Resolving Nonperforming Loans in the Republic of Korea - He, Dong (IMF Working Papers; Working Paper ;, 2004)
This paper aims to provide a balanced assessment of Korea Asset Management Corporation's role in resolving nonperforming loans in the aftermath of the 1997-98 financial crisis. It argues that KAMCO's incentive to dispose of NPLs can be explained by a strong social desire for a recovery of public funds injected for financial sector restructuring. KAMCO's market-making role also helped overcome informational and coordination problems in the development of a market for distressed assets.